Delegation and information revelation - Axel Gautier; Dimitri Paolini (Fondazione Eni Enrico Mattei (FEEM), 2000)
This paper addresses the question of delegation in an organisation where there is an initial asymmetry of information between the principal and the agent. We assume that the principal cannot use revelation techniques à la Baron Myerson to elicit agent's superior information and in contrast, we posit that the decision and the state of the world parameter cannot be contracted for. With these simple contracts, we show that delegation is an alternative to contracting to elicit agent's information. We can show that delegated decisions completely reveal the state of the world to the principal. Therefore the principal can extract agent's information by giving up the control right over some decisions. As the organisation takes a sequence of decisions, the information learned by the principal can be used for the other decisions. So delegation is only partial: the principal delegates some decisions and keeps control over others.
Keywords: D23; D82; L22; 330; Incomplete contracts; delegation; signalling game; Spieltheorie; Signalling; Prinzipal-Agent-Theorie; Vertragstheorie; Asymmetrische Information; Theorie